Effect of titanium dioxide on the mechanical properties of 3D printed short carbon-fibers composite - Bandar Almeshari; Harri Junaedi; Muneer Baig; Abdulhakim Almajid (Journal of Materials Research and Technology)
This work aims to enhance the properties of 3D-printed polypropylene (PP) composites by adding short carbon fibers (SCF) and titanium dioxide nanoparticles (TiO2 NPs) as filler materials. For this purpose, three types of polypropylene (PP) matrix-based composite systems were developed: SCF/PP composites, TiO2/PP composites, and SCF/TiO2/PP (hybrid) composites. These composite pellets were further processed into filaments using a single screw extruder followed by a filament winder. The resulting composite filaments had various filler contents. The TiO2 NPs content in TiO2/PP composites was set at 2%, 4%, and 8%. Whereas, in the hybrid SCF/TiO2/PP system, the composition included 11% SCF with either 1% or 2% TiO2 NPs. Test samples were fabricated using a fused deposition modeling (FDM) 3D printer to evaluate the mechanical and morphological properties of the printed samples. The addition of TiO2 in TiO2/PP composites significantly improved their impact strength. Specifically, the impact strength of the 8% TiO2/PP and 11%SCF/2%TiO2/PP composites increased by 500% and 120%, respectively, when compared to the neat PP. The impact toughness of the 11%SCF/2%TiO2/PP composite also increased by 32% compared to the 11%SCF/PP composite. The innovation of this work lies in significantly improving the impact strength and toughness, especially in 8%TiO2/PP and 11%SCF/2%TiO2/PP composites, while maintaining print quality.